SOSIALISASI KEWIRAUSAHAAN DI DUSUN BOLAWEN TLOGOADI MLATI SLEMAN YOGYAKARTA - Hapsari Dyah Herdiani Herdiany; Latifah Putranti; Pradita Nindya Aryandha; Chandra Wisnu Utomo (Empowerment Journal, 2022)
This Community Service was carried out in the Bolawen Hamlet Community, Tlogoadi, Mlati, Sleman, Yogyakarta. The theme raised relates to the importance of cultivating an entrepreneurial spirit. The purpose of this community service activity is to understand entrepreneurship.Â Increase creativity in entrepreneurship, Encouraging the creation of jobs, Improving the village economy. The service carried out in Bolawen Hamlet was carried out using the lecture, discussion, and question and answer methods. The existence of samples of business products increases the interest of participants so that other business ideas emerge. Participants in this activity are dominated by productive age, where the enthusiasm in receiving material about entrepreneurship is very visible. The enthusiasm of the participants in this community service activity added to the sense of enthusiasm in interacting, so that there were no obstacles in the activity and it ran as expected. This service was carried out on Tuesday, February 11 and 18 2020. The smooth running of this service activity was supported by the Bolawen Hamlet community who gave a positive response and proved that the purpose of this service activity was running smoothly and successfully.